Aplikasi Manajemen Praktikum Laboratorium Software Engineering Sistem Komputer Universitas Diponegoro - Diaz Wicaksono; Kodrat Iman Satoto; Rinta Kridalukmana (Jurnal Teknologi dan Sistem Komputer, 2014)
Lab activities are activities that are routinely performed by college students, lab activities shall be carried out as part of the lectures. In practice, there is no doubt often occur int the organization of costraints associated with the lab, such as information dissemination, creation of assessment list and data is not centralized. One of the lab activities is performed in the Laboratory of Computer System Software Engineering Diponegoro University. The labs require a lab managementapplications in order to improve work efficiency and improve the smooth operation of the lab. Practical Application Management consist of client and a blogapplications, created using Visual C# for client, ASP.NET for the blog and with the .NET Framework technology also Microsoft SQL Server databases. Development method was performed using the waterfall method, whereas in application design using UML modeling. The expected result from design of this application is to create an application that consist of client and blog application to managedata from many lab activities in a university lab, such as processing data from various laboratory practitioner, creation of assessment list and dissemination of information about the lab activities.